Kepadatan Populasi Kepiting Bakau (Scylla Paramamosain Estampador) Pada Kawasan Hutan Mangrove Di Teluk Buo Kecamatan Bungus Teluk Kabung Padang Sumatera Barat - Muslimaini, Muslimaini; Nurhadi, Nurhadi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The existence of mangrove crab (S. paramamosain) in the Teluk Buo almost extinct. This is due to the arrest of mangrove crabs (S. paramamosain) continuously (overfhising) it conducted by the communities around there for sale or for food everyday. Also in the area of the Teluk Buo has never done research on population of S. paramamosain. The purpose doing this research was to determine the population density of S. paramamosain and to determine the physico-chemical factors on habitat water in Mangrove forest area in the Teluk Buo Kecamatan Bungus Teluk Kabung Padang West Sumatra. This research uses a descriptive survey, the research is based on selecting the location of the selected Mangrove vegetation so choose 3 stations. At every station there were 10 points (raps). Based on the results of the research showed that the population density of S. paramamosain about 1.4 individuals/trap water chemistry and physical factors in mangrove forest in the Teluk Buo Kecamatan Bungus Teluk Kabung Padang West Sumatra is also still in good tolerance for habitat of S. paramamosain.Â Â